Road traffic deaths and injuries in Kathmandu - Kuikel, Jyoti; Aryal, Bhagwan; Bogati, Tilak; Sedain, Bhagabati (Journal of Health Promotion, 2022)
Road accidents account for the eighth leading cause of death for all ages in the world. The roads in Nepal are one of the most dangerous in the world, putting road users at greater risk, due to geographical and human causes. Pedestrians, motorbikes, and cyclists are the most vulnerable road users in the Kathmandu Valley. This paper aims to describe the trend of road traffic deaths and injuries in Kathmandu from the perspective of a safer road user policy. A descriptive retrospective study was done based on the information provided by the Metropolitan Traffic Police on road traffic crashes. In the study, the data on road traffic crashes, injuries, and deaths from all types of vehicles over five successive years were obtained from Traffic Police Office, Kathmandu in March-November, 2020 whereas, all the existing national road safety policies and strategies were collected from secondary data. The collected data were analyzed through MS Excel and represented in tables, bar diagrams, and pie charts. From the five successive years’ trend on road traffic injuries and deaths in Kathmandu, it was analyzed that the number of road traffic accidents in FY 2019/20 was 1.5 times higher than in 2018/19. The fatality rate increased to 0.4 per 100,000 population in FY 2019/20 where the fatality of the male population was higher than that of females and the majority of them were of the age group 16-35 years. The death and injury ratio was calculated which showed that the ratio was higher in FY 2019/20 indicating mild injuries and 2 severe injuries. The main causes of traffic accidents were road user negligence, speeding, and overtaking operations. In conclusion, the majority of the young population is prone to be at risk of road traffic accidents and deaths which are preventable.